Pemberdayaan Ekonomi Masyarakat di Kampung KB Dusun Padang Assitang - Sharief, Suchi Avnalurini; M, Azrida; Thamrin, Halida (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
The purpose of this activity is to increase public knowledge about the benefits and side effects, especially the long-term contraceptive method and economic empowerment of the community in Kampung KB through productive activities, namely making milkfish nuggets. The implementation method is to provide counseling related to long-term contraceptive methods, socialization of benefits and how to make milkfish nuggets, as well as packaging and marketing of milkfish nuggets. The results of this activity There was an increase in understanding where the results of the pretest were carried out on 12 mothers who were given a questionnaire with 10 questions consisting of the results of the pretest mothers, namely 50% had good knowledge, 33% had sufficient knowledge, and 17% had less knowledge. After being given counseling, there was an increase in knowledge, namely 83% good, 17% sufficient and no longer lacking knowledge of long-term contraceptive methods. The UPPKS mentari group has been able to make milkfish nuggets independently with simple packaging and has been equipped with a label so that it can become a product worthy of sale.